Investigation of the ndvB gene related to antibiotic resistance in a biofilm of Pseudomonas aeruginosa isolates in Iraq - Al-Maeni, Mohammad Abdul Rahmman (Iraqi Journal of Science, 2025)
The high morbidity and mortality are caused by Pseudomonas aeruginosa, which behaves as an opportunistic organism that resists many disinfectants through biofilm. The current study aims to detect variation in the ndvB gene and its relation with biofilm construction through the correlation of the change in the DNA sequence of the ndvB gene in different isolates and their phenotypic change in biofilm formation (weak, moderate, and strong biofilm producers). The biofilm was constructed, and the Minimum Inhibitory Concentration (MIC) for planktonic cells and Minimum Bactericidal Concentrations (MBC) for biofilm-forming cells were determined for the 20 isolates under the study. The prevalence of ndvB gene was detected, and its sequence was detected through Sanger sequencing and compared to the analysis of the genic variation for the ndvB gene and their correlation with phenotypic change for biofilm construction. Most of the isolates were biofilm producers and were resistant to different antibiotics. In addition, MBC for biofilm-producing isolates was high, while MIC for the planktonic cell was low. This result may indicate the isolates can resist ciprofloxacin, gentamicin, and tobramycin antibiotics in the presence of biofilm. Furthermore, the SNP detection in the coding sequence of the ndvB gene in isolate with ID 14 compared with the reference genome revealed that SNP located at position 792 transferring G to A. This variation may contribute to the resistance of the ndvB gene to antibiotics in the presence of biofilm in P. aeruginosa but needs to be further proven experimentally.